Cochlear Synaptopathy Evaluation With Electrocochleography in Patients With Hearing Difficulty in Noise Despite Normal Hearing Levels - Yaşar, Murat; Öner, Fatih; Atalay, Fatma; Anbar, Sezai Sacid (Wiley, 2024)
ABSTRACTObjectiveThis study examined patients with normal hearing thresholds who had trouble understanding speech in noise. We used electrocochleography (ECochG) to detect and compare SP/AP amplitude area ratios, a potential indicator of cochlear synaptopathy, and investigate speech perception disorder in noise.MethodsThe study included 68 people aged between 18 and 65 years, 35 patients and 33 healthy volunteers, who applied to the otorhinolaryngology clinic between November 2023 and March 2024 with a 2‐month history of difficulty understanding speech in noisy environments. Everyone was given a tiptrode electrode ECochG test, and the results were compared between groups. An ECochG test was recorded with tiptrode electrodes and was performed on all participants, and the results were compared between groups.ResultsIn the ECochG test, the summation potential/action potential (SP/AP) amplitude and area ratios of patients who had difficulty understanding speech in a noisy environment were statistically higher than those of the control group.ConclusionECochG testing may provide additional evidence to evaluate auditory nerve pathways.
Keywords: Adult; Male; Adolescent; Auditory Threshold; Middle Aged; Audiometry, Evoked Response; Cochlea; Young Adult; Case-Control Studies; Speech Perception; Humans; Original Article; Female; Hearing Loss, Hidden; Noise; Aged